2012
DOI: 10.1080/09593330.2011.646317
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of cigarette filter rods as a biofilm carrier in an anaerobic moving bed biofilm reactor

Abstract: Biocarriers are an important component of anaerobic moving bed biofilm reactors (AMBBRs). In this study, the capability of cigarette filter rods (CFRs) as a biocarrier in an anaerobic moving bed biofilm reactor was evaluated. Two similar lab-scale anaerobic moving bed biofilm reactors were undertaken using Kaldnes-K3 plastic media and cigarette filter rods (wasted filters from tobacco factories) as biofilm attachment media for wastewater treatment. Organic substance and total posphours (TP) removal was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, there can be productive uses for cigarette butts. For example, they have been used as a media for biofilm growth in anaerobic digestors (Sabzali et al 2012). Cigarette filters have also been used to store energy by heat treating them under a nitrogen atmosphere to prepare N-doped mesoporous / microporous carbon material (Minzae et al 2014).…”
Section: Alternative Uses For Cigarette Buttsmentioning
confidence: 99%
“…However, there can be productive uses for cigarette butts. For example, they have been used as a media for biofilm growth in anaerobic digestors (Sabzali et al 2012). Cigarette filters have also been used to store energy by heat treating them under a nitrogen atmosphere to prepare N-doped mesoporous / microporous carbon material (Minzae et al 2014).…”
Section: Alternative Uses For Cigarette Buttsmentioning
confidence: 99%
“…Ou et al successfully recycled CBs into oileophilic fibers, which remained efficient after 10 experimental runs 31 . The biofilm carrier prepared from CB recycling in the study by Sabzali et al showed similar performance as commercial samples used in wastewater treatment 22 .…”
Section: Introductionmentioning
confidence: 85%
“…However, numerous studies with encouraging findings have been published on recycling CBs in recent years, such as extraction of trapped chemicals in CBs for vector control 20 , 21 . Numerous attempts have been made in this field, for instance, the production of biofilm carriers used in wastewater treatment 22 , carbon adsorbents 23 , 24 , bricks and asphalt 25 , 26 , sound absorbers 27 , and paper pulp 28 from CBs have been investigated in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Carriers are usually designed to have a large protected surface on which biofilm can grow, such as K1-K5, sponges-HDPE, polyurethane foam (PUF), PUF-PP, and Mutag Biochip (Ødegaard et al 1994;Araujo Junior et al 2013;Bassin et al 2016;Saidi et al 2017;Sonwani et al 2019). However, alternative carriers with lowcost and recycled material have been employed in MBBR to overcome the economic limitations, such as a recycled corrugated tube, recycled plastic, and cigarette filters rods from tobacco factories (Wolff et al 2005;Sabzali et al 2012;Tombola et al 2019).…”
Section: Introductionmentioning
confidence: 99%